A randomised placebo controlled trial of delipidated, deglycolipidated Mycobacterium vaccae as immunotherapy for psoriatic arthritis. Issue 6 (12th May 2004) - Dalbeth, N; Yeoman, S; Dockerty, J L; Highton, J; Robinson, E; Tan, P L; Herman, D; McQueen, F M
Abstract : Objectives: To test the hypothesis that PVAC, delipidated, deglycolipidated heat killed Mycobacterium vaccae, is an effective and safe treatment for psoriatic arthritis (PsA). This treatment has shown promising results in psoriasis. Methods: 36 patients with PsA in two centres were studied in this double blind, placebo controlled, randomised trial. Patients were randomised to receive two intradermal injections of 50 µg PVAC or placebo and were followed up for 24 weeks. The primary end point was the Psoriatic Arthritis Response Criteria (PsARC), a composite measure based on changes in joint tenderness and swelling scores and physician and patient global assessments. Results: The PsARC response at either 12 or 24 weeks was achieved by 9/18 (50%) placebo and 9/18 (50%) PVAC patients (p = 1.0). No significant differences in the Psoriasis Activity and Severity Index (PASI), patient or physician global assessments, CRP, or Health Assessment Questionnaire score over time were found between the two groups. However, changes in the pain visual analogue scale over time did differ between the two groups (p = 0.006): at 24 weeks the mean score in the PVAC group had declined by 19.2 mm and in the placebo group had increased by 4.8 mm. PVAC was well tolerated with no increased incidence of adverse events compared with placebo. Conclusions: PVAC was not shown to be as effective as immunotherapy for PsA. The striking response to placebo in this study reinforces the importance of adequately controlling therapeutic trials in PsA.